Health risk assessment of metals in mud crab (Scylla serrata) from the East Java Estuaries of Indonesia - Soegianto, Agoes; Holy Ichda Wahyuni; Yulianto, Bambang; Abd Manaf, Latifah (Elsevier, 2022)
Metals accumulating in mud crab from Indonesia's East Java estuaries have been assessed for potential health effects. Mud crabs from the Solo River estuary (JS) had the highest levels of all metals tested when compared to mud crabs from the Brantas River estuary (MS) and the Banyuwangi coastal area (BS). Metal accumulation in mud crabs occurred in the following order: Zn > Cu > Cr > Pb > Cd > Hg. The estimated weekly intake values for all metals from all stations were less than the provisional tolerable weekly intake requirement. Similarly, all metal target hazard quotient values from all stations were less than one, suggesting that all metals were within the allowable intake limit. The target cancer risk values for Cd and Cr, on the other hand, were somewhat higher than 10-4, indicating that they were dangerous for human ingestion and possibly linked to a risk associated with carcinogenic agent exposure over a lifetime.